Afstand, modstand og mestring: Poetiske analyser af unges subjektiveringsprocesser - Görlich, Anne (Psyke & Logos, 2016)
An increasing number of young people under the age of 30 are neither in education nor in employment. Politically, as well as in the academic world, there is an interest in finding out ‘what works’ in order to help the young. However, there is also a lack of research in Denmark, which explores the complexity of this subject matter. Using poetic inquiry as the method, this article aims to investigate how subjectivities of young people at the margins of education are formed in processes in which education is the vehicle. Poetic inquiry gives access to the complexity that characterizes the problem area related to young people at the margins of education, and this article will explore the versatility of processes of subjectification in the politically influenced context in which education is seen as the solution. The analyzes show how various forms of ‘distance’ influence the processes of subjectification and how this occurs in processes of simultaneous submission and mastery of those forms of distance.